2021
DOI: 10.5897/ajmr2021.9475
|View full text |Cite
|
Sign up to set email alerts
|

Resistance profile of Salmonella isolated from food sold in the streets of NDjamena, Chad

Abstract: The preparation and sale of street foods is booming in African cities in general and especially in N'Djamena. However, the hygienic failures observed during this activity constitute a source of contamination of these foods. The objective of this work is to determine the different serotypes of Salmonella isolated from food sold in the streets of N'Djamena in Chad and to test their sensitivity antibiotics. In total, 447 samples from 12 different types of food were collected and analyzed using standard food micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…In Chad, Bessimbaye et al (2013) in their study showed that most diarrheal diseases are due to coliforms and especially pathovars of E. coli, Salmonella enterica and Shigella, Mayoré et al (2021), show the occurrence and antimicrobial resistance of Salmonella sp. from street food collected in Chad.…”
Section: Introductionmentioning
confidence: 99%
“…In Chad, Bessimbaye et al (2013) in their study showed that most diarrheal diseases are due to coliforms and especially pathovars of E. coli, Salmonella enterica and Shigella, Mayoré et al (2021), show the occurrence and antimicrobial resistance of Salmonella sp. from street food collected in Chad.…”
Section: Introductionmentioning
confidence: 99%